Analysis of the Effect of Brand Experience and Brand Love Toward Resistance to Negative Information of the McDonald’s Brand - Puti Syifa Azzahra; Putri Lathifah 'Afif; Christian Haposan Pangaribuan (President University, 2023)
People spend their money impulsively on things they love in this modern age. They claim it is brand love and often do not realize how much they have spent on it. Using McDonald’s as the brand, the main focus of this study was to analyze the effect of brand experience and brand love on resistance to negative information about a brand. This research is classified as a descriptive analysis method to take samples and a questionnaire as the primary tool. Ninety-nine out of 142 McDonald’s customer from around Indonesia was used as a sample for this research. Respondents were selected using a non-probability sampling technique. The research results demonstrate that just because someone has used or tried a brand’s product doesn’t mean they will automatically become resistant to information about the brand. They must first cultivate a brand-love attitude toward the brand.